2021
DOI: 10.3390/plants10040625
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Based Modified Biostimulant (Copper Chlorophyllin), Mediates Defense Response in Arabidopsis thaliana under Salinity Stress

Abstract: To date, managing salinity stress in agriculture relies heavily on development of salt tolerant plant varieties, a time-consuming process particularly challenging for many crops. Plant based biostimulants (PBs) that enhance plant defenses under stress can potentially address this drawback, as they are not crop specific and are easy to apply in the field. Unfortunately, limited knowledge about their modes of action makes it harder to utilize them on a broader scale. Understanding how PBs enhance plant defenses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 115 publications
0
11
0
Order By: Relevance
“…Cu-chl has been shown to be protective against the effects of drought stress in tomatoes, where the frequent application of Cu-chl-containing materials improved the activity of leaf antioxidant enzymes as well as GSH concentration [ 249 ]. Islam et al [ 250 ] reported other functions of Cu-chl with respect to the development of tolerance against high salinity stress in A. thaliana . Soil salinity significantly decreases RWC with a concomitant increase in lipid peroxidation, total phenolics and cell membrane permeability.…”
Section: Nutrient Management Approaches To Alleviate the Abiotic Stre...mentioning
confidence: 99%
“…Cu-chl has been shown to be protective against the effects of drought stress in tomatoes, where the frequent application of Cu-chl-containing materials improved the activity of leaf antioxidant enzymes as well as GSH concentration [ 249 ]. Islam et al [ 250 ] reported other functions of Cu-chl with respect to the development of tolerance against high salinity stress in A. thaliana . Soil salinity significantly decreases RWC with a concomitant increase in lipid peroxidation, total phenolics and cell membrane permeability.…”
Section: Nutrient Management Approaches To Alleviate the Abiotic Stre...mentioning
confidence: 99%
“…Given the diverse and varied nature of the starting materials from which biostimulants can be obtained, they have been grouped into seaweed extracts, plant extracts, vegetal and animal protein hydrolysate, microorganisms, and humic and fulvic substances [16,17]. Some recent studies have also pointed out as biostimulants of various origins can improve the resistance of diverse plants to salt stress thanks to the upregulation of genes involved in stress tolerance, the improvement of nutrient uptake and pigments production, or decreasing oxidative stress [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Bioeffectors (biostimulants), compounds of biological origin that are applied to embellish nutrient uptake, stimulate growth and enhance stress tolerance or quality traits of crops ( Van Oosten et al, 2017 ), through stimulation of the plant’s metabolic and defense mechanisms. Exogenous application of several bioeffectors such as copper chlorophyllin (Cu-chl), a semi-synthetic water-soluble chlorophyll derivative ( Islam et al, 2021 ), Moringa oleifera leaf extract ( Desoky et al, 2018 ), and Ascophyllum nodosum extracts ( Dell’Aversana et al, 2021 ) have been shown to enhance salinity stress tolerance in A. thaliana , sorghum, and tomato, respectively. Plant-based bioeffectors therefore form part of the sustainable approach to enhance salt stress tolerance in crops and could potentially address breeding handicaps, as they are versatile and are easy to apply in the field.…”
Section: Salinity Management Using Secondary Metabolites and Microorganisms In Finger Milletmentioning
confidence: 99%